Comparison of childhood trauma levels in different ethnic structures in Turkey: Turkish, Kurdish, Zaza sample - Barut, Sümeyye; Baransel, Esra Sabancı; Uçar, Tuba; Çelik, Osman Tayyar (Selcuk University, 2023)
Purpose: Adverse childhood experiences and traumas are common. The determination of the rates of these negativities at the level of ethnicity is important in terms of health approaches. In this study, it was aimed to compare the negative childhood experiences and childhood trauma levels in different ethnic structures in Turkey. Methods: This cross-sectional study was collected using a web-based online questionnaire through men's and women's groups on Facebook. Individuals between the ages of 18-49, ethnically Turkish, Kurdish or Zaza, who could read Turkish were included in the study. Participants who were determined to have filled the questionnaire incompletely or carelessly were excluded from the study, and the study was completed with 815 participants. The data of the study were collected using the Descriptive Characteristics Determination Form and Childhood Traumas (CCT), which includes sociodemographic characteristics and some negative experiences in childhood. Results: It was determined that the physical, emotional and sexual abuse sub-dimension mean score of individuals with Kurdish ethnicity was higher than individuals with Turkish and Zaza ethnicity, and the difference between the groups was statistically significant (p

Amaç: Olumsuz çocukluk çağı deneyimleri ve travmalar yaygın oranlarda görülmektedir. Bu olumsuzlukların oranlarının etnik yapı düzeyinde belirlenmesi, sağlık yaklaşımları açısından önemlidir. Bu çalışmada Türkiye’de farklı etnik yapılardaki olumsuz çocukluk çağı deneyimleri ve çocukluk çağı travma düzeylerini karşılaştırmak amaçlandı. Yöntem: Kesitsel nitelikte olan bu çalışma Facebook’ta yer alan kadın ve erkek grupları aracılığıyla web tabanlı bir çevrimiçi anket kullanılarak toplandı. Araştırmaya 18-49 yaş aralığında, etnik yapısı Türk, Kürt veya Zaza olan, Türkçe okuyabilen bireyler alındı. Anket formunu eksik veya dikkatsiz doldurduğu belirlenen katılımcılar çalışmadan dışlanarak 815 katılımcı ile çalışma tamamlandı. Araştırmanın verileri sosoyodemografik özellikleri ve çocukluk çağında yaşanan bazı olumsuz deneyimleri içeren Tanımlayıcı Özellikleri Belirleme Formu ve Çocukuluk Çağı Travmaları (ÇÇTÖ) kullanılarak toplandı. Bulgular: Kürt etnik yapıya sahip bireylerin fiziksel, duygusal ve cinsel istismar alt boyutu puan ortalaması Türk ve Zaza etnik yapıya sahip bireylere göre daha yüksek olduğu ve gruplar arasındaki farkın istatistiksel olarak anlamlı olduğu belirlendi (p0.05). Zaza’ların %23.7’sinin aile içi fiziksel şiddete tanık olduğu, Kürt’lerin %16.3’ünün ayrımcılığa maruz kaldığı, Zaza’ların %26.0’sının aile dışı fiziksel şiddete tanık olduğu, Kürt’lerin %21.7’sinin hırsızlık tanığı/mağduru olduğu, Zaza’ların %16.0’sının yakınından birinin öldürüldüğüne tanık olduğu, Kürt’lerin %27.5’inin isyanlara tanık olduğu, Kürt’lerin %9.5’inin savaş ortamında bulunduğu ve gruplar rasındaki farkın istatistiksel olarak anlamlı olduğu belirlendi (p
TÜRKİYE’DE FARKLI ETNİK YAPILARDA ÇOCUKLUK ÇAĞI TRAVMA DÜZEYLERİNİN KARŞILAŞTIRILMASI: TÜRK, KÜRT, ZAZA ÖRNEĞİ
Keywords: Clinical Midwifery; Klinik Ebelik